Investigation of dimethyl sulfide formation during GC analysis of permethrin API: study of the reaction kinetics and estimation of the activation energy of the reaction. Issue 86 (1st September 2016) - Tian, Jingzhi; Rustum, Abu
Abstract : Dimethyl sulfide was formed via a reaction between dimethyl sulfoxide and 3-phenoxylbenzyl chloride during gas chromatography analysis of the active pharmaceutical ingredient permethrin (PMN). The kinetics and the activation energy of the reaction are presented herein. Abstract : An unknown peak in the chromatogram was observed during gas chromatography (GC) analysis of the active pharmaceutical ingredient (API) permethrin (PMN). Further investigations revealed that the identity of the unknown peak is dimethyl sulfide (DMS) which was formed via a reaction between dimethyl sulfoxide (DMSO) and one of the impurities of PMN named 3-phenoxylbenzyl chloride. Kinetics of the reaction was studied and the activation energy of the reaction was determined through Arrhenius analysis.